Social Inequalities in Tooth Loss Over Time: Insights From Australian Adults - Xiangqun Ju; Liana Luzzi; Sergio Chrisopoulos; Gloria C. Mejia; Lisa M. Jamieson (International Dental Journal)
Introduction and aim: In contemporary society, social inequality in tooth loss is a significant and often overlooked issue. This study aimed to describe and examine social differentials in tooth loss among Australian adults over time. Methods: This analysis used data from the National Survey of Adult Oral Health (NSAOH), which was conducted in Australia in 2 waves: NSAOH-1 (2004-2006) and NSAOH-2 (2017-2018). The study employed a population-based cross-sectional design, with adults aged 15 years and older randomly selected using a 3-stage, stratified sampling method across metropolitan and regional areas in each state and territory. The primary outcomes were self-reported edentulism and non-functional dentition (<21 teeth). Explanatory variables included socioeconomic status, assessed using equivalized household income and grouped into approximate quartiles from lowest to highest, along with sociodemographic factors, CALD (Culturally and Linguistically Diverse) status, and oral health-related behaviour. Unadjusted and adjusted absolute prevalence differences (PDs) were calculated to assess income-related inequality. Adjustments were made for age and sex using the average covariate distribution across all income groups. Results: Data were available for 14,123 participants in NSAOH-1 and 15,731 participants in NSAOH-2. The prevalence of edentulism declined from 6.4% to 4.0%, and non-functional dentition decreased from 17.1% to 13.8% over time. These reductions were observed across all household income quartiles, with lower prevalence rates for both conditions in NSAOH-2 compared to NSAOH-1. The adjusted model showed that the prevalence decreases were most marked for the lowest household income group, from 15.3 to 6.5 (PD = 8.8, 95% CI: 8.3-9.4) for edentulism and from 35.0 to 21.3 (PD = 13.7, 95% CI: 13.4-14.0) for non-functional dentition. Conclusion: Our study indicated social inequalities in both edentulism and non-functional dentition among Australian adults over time. Age, sex, place of residence, irregular dental visits, and lack of dental insurance were important factors associated with tooth loss.